António M. Lopes Andrade - Carlos De Miguel Mora - Joâo M. Nunes Torrâo (coords.), Humanismo e ciencia. Antiguidade e Renascimento, Aveiro - Coimbra - Sâo Paulo, UA Editora - Universidade de Aveiro - Imprensa da Universidade de Coimbra - Annabluem, 2015 (Minerva, 2017)
Reseña del libro António Manuel Lopes Andrade - Carlos De Miguel Mora - Joâo Manuel Nunes Torrâo (coords.), Humanismo e ciencia. Antiguidade e Renascimento, Aveiro - Coimbra - Sâo Paulo, UA Editora - Universidade de Aveiro - Imprensa da Universidade de Coimbra - Annablueme, 2015, 541 pp., ISBN UA 978-972-789-434-5 / IUC 978-989-26-0940-9